Pengaruh Live Streaming, Influencer Marketing dan Flash Sale Terhadap Keputusan Pembelian Pada Produk Skincare Lokal - Tiara Insan Salamah; Jonet Ariyanto Nugroho (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to examine: (1) the effect of live streaming on Generation Z’s purchasing decisions for local skincare products in Surakarta, (2) the effect of influencer marketing on purchasing decisions, (3) the effect of flash sales on purchasing decisions, and (4) the indirect effects of these variables through purchase intention. The population consists of Generation Z in Surakarta aged 15–28 years who are active on social media and use local skincare products, with a sample of 150 respondents selected using purposive sampling. Data were collected via a Google Forms questionnaire, with validity tested using the Product Moment method and reliability using Cronbach’s Alpha. The data analysis included descriptive statistics, normality, linearity, multicollinearity, heteroscedasticity, and path analysis. The results show that live streaming has a positive and significant effect on purchasing decisions, indicating that interactive demonstrations increase consumer trust and purchase behavior. Influencer marketing shows no significant effect, suggesting that endorsements alone do not strongly influence Generation Z’s decisions. Flash sales have a positive and significant impact, proving that limited-time discounts effectively stimulate purchases. Furthermore, purchase intention partially mediates the effects of live streaming and flash sales on purchasing decisions, although the indirect effect is relatively small. Meanwhile, purchase intention does not mediate the influence of influencer marketing. Overall, interactive strategies such as live streaming and promotional tactics like flash sales are more effective than influencer endorsements in shaping Generation Z’s purchasing decisions for local skincare products in Surakarta. Keywords: live streaming, influencer marketing, flash sale, purchase decision, purchase intention